Influence of Aluminium Concentration on the Properties of Spray Deposited CdAlS Thin Films - Rajathi1, S.; Sankara Subramanian2, N.; Ramanathan2, K.; Senthamizhselvi1, M.; Vasuki2, R.; Shanmugam3, S. (Asian Journal of Chemistry, 2013)
Aluminium doped cadmium sulphide (CdAlS) thin films have been spray deposited on mineral glass substrate fixed at 400 ºC, with varying aluminium concentration (from 0.002 to 0.01 mol %). The XRD profile of CdAlS thin films confirm the hexagonal structure with the preferred orientation along the (002) plane. The lattice constant evaluated from the XRD data a = 4.135 Å and c = 6.7489 Å are well in agreement with the standard JCPDS values (PDF file No. 77-2306). The average crystallite size calculated from the XRD data lies between 300 and 400 nm. Other crystallographic parameters viz., texture coefficient, standard deviation, lattice strain and dislocation density have also been calculated. Optical transmittance of the films has been recorded in the wavelength region 300-800 nm using UV-visible spectrophotometer. From the transmittance measurements, the optical constants viz., extinction and absorption coefficient have been evaluated. The band gap energy estimated from the optical data lies between 2.3 eV and 2.4 eV. Surface features of the films have been investigated form the SEM micrograph images. The effect of aluminium concentration on the properties of the spray deposited CdAlS thin films have been analyzed in detail and presented.